Inhibitory effect of post-hemorrhagic shock mesenteric lymph drainage on the HMGB1 and RAGE in mouse kidney. (2nd January 2016) - Liu, Gui-Qing; Zuo, Xian-Hong; Jiang, Li-Na; Zhang, Yu-Ping; Zhang, Li-Min; Zhao, Zi-Gang; Niu, Chun-Yu
Abstract: Background : Excessively inflammatory response is one of mechanisms that underlie the acute kidney injury (AKI) induced by severe hemorrhagic shock, which could be ameliorated by post-hemorrhagic shock mesenteric lymph (PHSML) blockage. Recent studies demonstrate that high mobility group box 1 (HMGB1) and the receptor for advanced glycation end products (RAGE) are critical mediators of local inflammations. The present study was sought to investigate whether the PHSML drainage inhibits the HMGB1 and RAGE in mouse kidney to ameliorate the renal inflammatory responses. Methods : A mouse hemorrhagic shock model (40 ± 2 mmHg for 90 min, fluid resuscitation for 30 min) was employed, and the PHMSL drainage was performed at the end of the resuscitation. After 3 h of resuscitation, the expressions of mRNA and protein for the renal HMGB1 and RAGE and the levels of interleukin (IL)-1β and IL-18 were assessed by the real-time reverse transcription-polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. Results : Hemorrhagic shock elicited significant increases in the mRNA expressions of HMGB1 and RAGE and in the protein expressions of HMGB1, RAGE, IL-1β and IL-18 in kidney. The PHSML drainage abolished these potentiating effects. Conclusion : The present study demonstrates that PHSML blockade reduces the increased HMGB1 and RAGE and pro-inflammatory factors following hemorrhagic shock, suggesting that the PHSML elicits the inflammatory responses via enhancing the HMGB1 and RAGE production in the kidney.